Clinical significance of estrogen receptor β in breast and prostate cancer from biological aspects. Issue 4 (9th March 2015) - Omoto, Yoko; Iwase, Hirotaka
Abstract : Breast and prostate cancers are among the most common of all cancers. They are referred to as hormone‐dependent cancers, because estrogen and androgen are involved in their development and growth. The effects of these hormones are mediated by their respective receptors, estrogen receptor (ER) α and androgen receptor. Around 18 years ago, a second ER, ERβ, which has a very similar structure to ERα, was discovered. Its function has been investigated using a variety of methods and biological systems, leading to our present understanding that ERβ can interact with or inhibit ERα and androgen receptor function directly and/or indirectly, suppress cell growth, and influence responsiveness to endocrine therapy. In order to apply the "inhibition of cell growth" function to cancer treatment, several specific ERβ agonists have been synthesized and are being tested for effectiveness in cancer treatment. We need to keep our eyes on ERβ. Abstract : Estrogen receptor β (ERβ) has been discovered in 1996 and its function was investigated with various way. ERβ can interact with or inhibit ERα and AR function directly and/or indirectly, suppress cell growth, and influence responsiveness to endocrine therapy. This manuscript summarize our knowledge about the significance of ERβ in breast and prostate cancer.